2021
DOI: 10.3390/healthcare9101283
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of Nepalese High-School Students in Cancer Awareness Using a Photovoice Based on the Health Belief Model

Abstract: Delivering cancer education is one of the strategies for implementing health promotion and disease prevention programs. Moreover, cancer education can help people understand the risks related to specific behaviors that can trigger cancer during later life stages. This study examines the cancer perception of high school students (median age: 14 years) using a photovoice based on the health belief model. Students were requested to take photographs to answer the framework question: “How is cancer present in your … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Many studies have confirmed that students’ perceptions and opinions are important references for the arrangement of educational programs [ 12 , 13 , 14 ], and collaboration between students and clinical faculties at internship hospitals can create effective educational programs [ 15 ]. Instructional media designed from the perspective of participants can help them follow instructions more effectively [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed that students’ perceptions and opinions are important references for the arrangement of educational programs [ 12 , 13 , 14 ], and collaboration between students and clinical faculties at internship hospitals can create effective educational programs [ 15 ]. Instructional media designed from the perspective of participants can help them follow instructions more effectively [ 16 ].…”
Section: Introductionmentioning
confidence: 99%